Foreign direct investment and its spillover :empirical evidence from Malaysia - Shirley, Lim Ai Li. (Universiti Malaysia Sarawak (UNIMAS), 2007)
This study is undertaken to examine the spillover effects throughout the technology transfer from Foreign Direct Investment (FDI) in Malaysia by using annual time series data which covering the period of 1970 to 2005. In this study, Augmented Dickey-Fuller (ADF) unit root test, Johansen and Juselius cointegration test and Granger causality test are applied to examine the relationship among Gross Domestic Product (GDP), FDI, import of machinery and domestic investment. ADF unit root test shows that all the variables are stationary at first difference whereas Johansen and Juselius test reveals the existence of one cointegrating vector which indicating a long run relationship between GDP, FDI, import of machinery and domestic investment. Consequently, we found out that FDI does not Granger cause to Malaysia’s GDP, import of machinery and domestic investment. This means the spillover effects of FDI do not exist in the case of Malaysia. However, GDP, import of machinery and domestic investment are the important factors in directing FDI inflows into Malaysia. This study has suggested some policies that can be carried out by the policy makers in order to attract more inflows of FDI into Malaysia.